Professional Reasoning and Occupational Therapist's Use of a Multi-Sensory Environment for Clients with Dementia. (1st September 2014) - Crowe, Jessica
ABSTRACT Aims: To examine the professional reasoning process of occupational therapists using multi-sensory environments (MSEs) to treat clients with dementia. Methods: This was a qualitative study design which used interviews to uncover the multi-faceted professional reasoning process used by occupational therapists when implementing MSE interventions for individuals with dementia. Results: Qualitative data analysis yielded three themes regarding the professional reasoning process of occupational therapists that use MSEs to treat clients with dementia. Clinicians use MSEs because the intervention emphasizes client-centered care; facilitates neural changes; and promotes emotional connections. Conclusions: Current evidence does not support the professional reasoning process which occupational therapists use when integrating the MSE into the occupational therapy plan of care. Further qualitative research is indicated to explore why occupational therapists continue to use interventions that are not evidence-based and to examine the process in which clinicians abandon current practice methods when research evidence does not support their use.